Implementation of Multi-Criteria Decision Making in PPPK Recruitment at the Department of Public Works, Spatial Planning, Housing, Settlement Areas, and Land Affairs of Riau Province - Andrianto Saputra; Octadino Haryadi (Yayasan Ibrahim Learning Centre Agam, 2026)
The recruitment process of Government Employees with Work Agreements (PPPK) at the Department of Public Works, Spatial Planning, Housing, Settlement Areas, and Land Affairs of Riau Province requires an objective and transparent evaluation system. This study aims to implement the Multi-Criteria Decision Making (MCDM) method as a decision support system to determine the most suitable PPPK candidates. The assessment is conducted based on several criteria, including educational qualifications, competencies, work experience, and selection results. Each criterion is assigned a weight according to its level of importance to produce an objective ranking of candidates. The results show that the MCDM method can support decision-makers in the PPPK recruitment process in a systematic, consistent, and accountable manner.